Scritture e pensiero: tra Oriente e Occidente - Della Pergola, Fabio (Il sogno della farfalla, 2011)
Starting from the analysis of some writings which have appeared in a book edited by G. Bocchi and M. Ceruti, Origini della scrittura. Genealogie di un’invenzione (Milano 2002; The origins of writing. The geneology of an invention), this article delves into the difference between left-to right writing (Semitic and Etruscan) and right-to-left writing (Greek-Latin.) Some scholars hypothesize that the direction of writing may depend on the predominance of the right or left semi-fields of the eyes, as a consequence of the predominance of one cerebral hemisphere over another, giving rise to a different way of interpreting reality. This article, on the other hand, hypothesizes the contrary; that is, as the strongly rational culture of the Greek logos imposed itself, one cerebral hemisphere began prevailing over the other and ultimately determined the direction of writing.